The role of Matthew’s ἀφίημι-logia in the decisions of the General Synod of the Dutch Reformed Church (DRC) in post-apartheid South Africa - Nel, Marius (Stellenbosch theological journal, 2016)
This article investigates the use of the verb ἀφίημι in selected pericopae in the Gospel of Matthew and the decisions of the General Synod of the Dutch Reformed Church (DRC) on forgiveness in the post-apartheid South Africa. It argues that while forgiveness is an important topic in Matthew that is interwoven with a number of other important theological themes, it has been a neglected theme in the decisions taken by the General Synod of the DRC since 1994. Not only are there no explicit references to Matthew’s understanding of forgiveness, but are neither of the two references to forgiveness in the Acta of six General Synod’s references to asking forgiveness by the DRC for its active participation in apartheid. The article concludes with a number of suggestions on how Matthew’s ethic of forgiveness can inform the South African reconciliation process without it being reduced to a timeless fixed formula.